Magazines in the driving seat - Robinson, Colin (Henry Stewart Talks, 2009)
The recent evidence to date from the USA, Is this true in the UK?, Offline advertising drives online search, Magazine and TV advertising drive search, What about purchasing?, Magazines equal TV, Engagement makes a difference, The American experience
Archived at 2022/11/27